THE EFFECT OF SERVICE QUALITY ON COMMUNITY SATISFACTION IN REGIONAL DRINKING WATER COMPANIES (PDAM) IN PROVIDING CLEAN WATER IN SINJAI REGENCY - Fitriana, Nurul; Sakawati, Herlina; Guntur, Muhammad (Jurnal Aktor, 2025)
This study aimed to determine the effect of service quality on customer satisfaction in the Regional Water Company (PDAM) in providing clean water in Sinjai District. Research methods used a quantitative survey method (survey reseach) using explanatory approach or explanatory research to determine the effect between variables. This research used incidental Sampling technique (accidental sampling). Data collection techniques used questionnaires and documentation. Data analysis techniques used descriptive statistical analysis and inferential statistical analysis to explain the influence between variables descriptive. The results obtained the level of service quality is at category either with indicators Tangible (tangible), Reliability (reliability), Responsifines (responsiveness), Assurance (assurance), and Empathy (empathy).Community satisfaction is in the category of very satisfied with the indicators Service procedures, terms of Service, clarity of service personnel,Discipline of service personnel,responsibility of service personnel, Ability of service personnel, speed of Service, fairness of Service,Politeness and friendliness of officers, fairness of service fees, certainty of costs Service, Certainty of service schedules, environmental comfort, and security service. Based on data analysis shows the quality of Service have a significant influence on customer satisfaction of water users clean drinking water company in Sinjai district with the level the percentage of influence of 40.5%. This shows that the importance quality of service for the implementation of services to provided results in accordance with what customers expect